Komitmen dan Kompensasi Terhadap Prestasi Kerja di PT Somit Karsa Trinergi Jakarta - Wibowo, Aditya Ari (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
PT Somit  Karsa Trinergi as a company engaged in one of the industrial automation in the industry where the work was related to high technology so that the necessary human resources who have the knowledge and expertise that is high on the field. For this study will examine two variables. The variable is the commitment and the compensation and its effect on work performance. This study aims to determine the extent of the commitment that employees and compensation of the company will improve the performance of the employee. This study will use multiple regression analysis. Regression analysis will examine whether there is influence of independent variables (independent variable) on the dependent variable (dependent variable) and the size of the effect. In this study, the dependent variable is job performance, while the independent variables include, commitment, and compensation. The results obtained in this study is that the commitment of a significant and positive effect on employee performance. Compensation positive and significant impact on employee performance and commitment and compensation together positive and significant impact on employee performance PT. Somit Karsa Trinerg.